An Organic/Inorganic Composite Gel Electrolyte Inducing Uniformly Lithium Deposition at High Current Density and Capacity. Issue 22 (25th October 2021) - Li, Xue; An, Xufei; Li, Yuhang; Chen, Likun; Guo, Shaoke; Wang, Ruikang; Huang, Ling; Li, Song; He, Yan‐Bing
Abstract: Although gel polymer electrolytes (GPEs) have attracted tremendous attention for lithium metal batteries due to their high ionic conductivity, high safety, and excellent adaptability, it is still challenging to suppress the uncontrollable lithium dendrite growth for GPEs. Here, an organic/inorganic composite gel electrolyte (PPPL) as GPEs is proposed, which is formed by ring‐opening polymerization reaction of poly(methyl vinyl ether‐alt‐maleic anhydride) (PMVE‐MA) and polyethylene glycol (PEG) in polymer matrix of poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP) embedded with Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) particles. The PMVE‐MA participates in the formation of a stable solid electrolyte interface (SEI) and the PEG greatly improves the flexibility of PPPL. The PPPL exhibits excellent performance in terms of a wide electrochemical window (4.7 V), high lithium transference number (0.59), and satisfactory mechanical strength (11 MPa). Besides, the PPPL contributes to the formation of stable and flexible SEI containing organic components and LiF on lithium metal, and constructs fast and uniform lithium transport channels to effectively suppress the lithium dendrite growth. The Li/PPPL/Li symmetric batteries can stably cycle 800 h at the high current density of 5 mA cm –2 and capacity of 5 mAh cm –2 . The outstanding electrochemical performance of the PPPL will provide important insights for design of advanced GPEs. Abstract : A multifunctional organic/inorganic composite gel polymer electrolyte (PPPL) is proposed by the reaction between poly(methyl vinyl ether‐alt‐maleic anhydride) (PMVE‐MA), polyethylene glycol (PEG), poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP), and Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO). The PMVE‐MA will form a stable solid electrolyte interface during cycling as a result of its low LUMO. The LLZTO can induce the uniform lithium deposition by its high ionic conductivity. The symmetric battery assembled with PPPL presents excellent cycle stability at high current density.